Maintaining Yogyakarta’s Market Traditions to Develop Islamic Trade in Indonesia - Utomo, Yuana Tri; Karim, Muhammad Abdul (Islamic Research, 2024)
The purpose of this study is twofold, namely: uncovering traditions in Yogyakarta's traditional markets in the face of free competition and developing them into Islamic trade clean from the influence of capitalism. Researchers used the main information from observations and interviews with traditional market participants, namely: one person from the Yogyakarta palace, one market authority, one trader, one buyer, and one person from the market association. Supporting information is taken from the researcher's readings on literature documents related to the research topic, such as articles that have been published in journals and library books. After the information is collected, it is then analyzed interactively throughout the research period by triangulating continuously until it is saturated. The results of this study show that traditional market traditions in Yogyakarta, such as market kekancingan, supervision by market lurah, kirab, and market grebeg, have been maintained from the onslaught of the free market so that it continues to exist until now because of the spirit of market players driven by Islamic motivation, namely worshipping Allah SWT. These traditions can be developed to be stronger to revive Islamic trade in an Islamic economic system that can match capitalism. This method of developing the tradition by adding a complete understanding of the concept of the market in the Islamic economic system. The findings of this study are expected to contribute to adding to the discourse of the market concept in Islamic economic studies and can practically be applied by the authorities for the protection of traditional markets from modern market attacks.